"I Don't Care About Asia": Teaching Asia in Australia. Issue 3 (3rd July 2017) - Leong, Susan; Woods, Denise
ABSTRACT: This paper argues that an important part of the work that remains to be done in Asian Australian studies is at the frontline of academia—teaching. In a world of contrarily increasing mobility and cultural apathy, how do we convey the relevance of Asia to students without resorting to the discourses of Asia as the exotic other and/or as a market? In what ways can "Asia literacy" be interpreted for a student body whose identities are becoming both more complex and syncretic? We suggest that university teachers are uniquely positioned to equip students with an understanding of Asia that is more processual than factual and more attitudinal than learnt. Drawing on the experience of teaching over a decade in Perth and Brisbane, we reflect on how the task has changed over the years, what the typical obstacles/barriers faced are, and what students understand Asia literacy to mean in the midst of the political and media discourses surrounding Asia today. Finally, we reflect on how our own experiences of such teaching emerges from our own sense of being and belonging as Australians of Asian origins.